Economic Sanctions, well-being, and the duty to trade - Arancibia-Collao, Fernando (Filosofia, 2023)
In this paper I would argue that, in the context of the ethics of economic sanctions, there is a duty to trade, and that duty is grounded in the practical and instrumental indispensability of trading for well-being of the people of the states. I understand well-being as the optimal conditions for survival and self-realization that states must warrant to people. I will answer the arguments against a duty to trade, as well as the arguments for a duty not to trade in those cases where the parties to the trade are dictatorships. I will develop my argument based on the metaethical argument about deliberative indispensability in favor of moral facts, developed by David Enoch, and raise an analogy with practical indispensability. The way of states to promote well-being is by trading. If trade is essential for survival, states have a strong prima facie duty to trade. If trade is not essential for survival, but nonetheless it is important for well-being, then states have a weak prima facie duty to trade.